Mind over Matter : Memory Fiction from Daniel Defoe to Jane Austen - Eron, Sarah, 1982- (Book collections on Project MUSE., 2021)
"Mind over Matter offers a new history of the early, eighteenth-century, novel in relation to empiricism's central claim about memory. Eron considers how memory's creative force empowers both characters and readers-how that force alters, reconstitutes, and even overcomes the conditions of our physical environment. Works discussed include those by Daniel Defoe, Frances Burney, Laurence Sterne, and Jane Austen"--